Sphyrna gilberti sp. nov., a new hammerhead shark (Carcharhiniformes, Sphyrnidae) from the western Atlantic Ocean - Quattro, Joseph M.; Driggers, William B. Iii; Grady, James M.; Ulrich, Glenn F.; Roberts, Mark A. (Zootaxa, 2013)
Sphyrna gilberti sp. nov. is described based on 54 specimens collected in the coastal waters of South Carolina, U.S.A. Morphologically, S. gilberti sp. nov. is separable from S. lewini (Griffith & Smith 1834) only in the number of precaudal vertebrae. Due to rarity of specimens and the highly migratory behavior of most sphyrnids, the range of S. gilberti sp. nov. is unknown.